2009
DOI: 10.1590/s0100-83582009000300023
|View full text |Cite
|
Sign up to set email alerts
|

Atividade residual de (imazethapyr+imazapic) sobre azevém anual (Lolium multiflorum), semeado em sucessão ao arroz irrigado, sistema clearfield®

Abstract: Palavras-chave: arroz-vermelho, arroz Clearfield ® , imidazolinonas, persistência no solo.ABSTRACT -The aim of this study was to evaluate the residual activity of the prepackage mix of the herbicide Only (imazethapyr+imazapic) in a Clearfield (CL) rice production system during one, two or three rice seasons. The study was carried out in the field at Centro Agropecuário da Palma/ Universidade Federal de Pelotas, Rio Grande do Sul, southern Brazil. Ryegrass (Lolium multiflorum) was planted after CL rice, cv. IRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
6
21
0
5
Order By: Relevance
“…In contrast, a dry matter reduction in all soil profile thicknesses occurred (Figure 2), which shows the herbicide carryover to ryegrass plants. These results are similar to those reported by Pinto et al (2009a), who found that imazethapyr + imazapic, applied at a 1.0 L ha -1 in post-emergence irrigated rice, remains active in the soil to significantly reduce the plant's aboveground dry height, its biological yield and the germination potential of ryegrass seed sown in rotation, after a year of CL rice cultivation. In contrast, Grohs et al (2008) showed no carryover effect on ryegrass emergence, and shoot dry weight.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, a dry matter reduction in all soil profile thicknesses occurred (Figure 2), which shows the herbicide carryover to ryegrass plants. These results are similar to those reported by Pinto et al (2009a), who found that imazethapyr + imazapic, applied at a 1.0 L ha -1 in post-emergence irrigated rice, remains active in the soil to significantly reduce the plant's aboveground dry height, its biological yield and the germination potential of ryegrass seed sown in rotation, after a year of CL rice cultivation. In contrast, Grohs et al (2008) showed no carryover effect on ryegrass emergence, and shoot dry weight.…”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, it may be adversely be affected by the herbicide residues in soil. Studies show that ryegrass seeds have reduced growth as well as dry matter when grown in imidazolinone treated areas (Pinto et al, 2009a).…”
Section: Podem Persistir No Ambiente E Causar Danos àS Culturas Não Tmentioning
confidence: 99%
“…Residual activity of these herbicides in the soil may manifest itself in subsequent crops in the form of phytotoxicity (KRAEMER et al, 2009), decrease in height (PINTO et al, 2009) and plant death. Allied to this, the increase in the dose of these herbicides promoted by the use of rice cultivars with higher levels of tolerance can exacerbate the problem of residual soil.…”
Section: Crop Protectionmentioning
confidence: 99%
“…This herbicide is characterized by long persistence in soil and show effect in dicotyledonous and monocotyledon, which reduces the number of applications, however, has reported cases of phytointoxication. Pinto et al (2009) when evaluating the application of a mixture of herbicides (imazethapyr + imazapic) in ryegrass culture in succession to irrigated rice, observed a phytotoxic effect of this mix, resulting in smaller plants, requiring a range of 180 days from the application until the sowing of the next crop, due to the possibility of this effect persist in soil for a long time, depending on the environment.…”
Section: Introductionmentioning
confidence: 99%